2023
DOI: 10.1002/ange.202210254
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations Guide Chimeragenesis and Engineered Control of Chemoselectivity in Diketopiperazine Dimerases

Abstract: In the biosynthesis of the tryptophan‐linked dimeric diketopiperazines (DKPs), cytochromes P450 selectively couple DKP monomers to generate a variety of intricate and isomeric frameworks. To determine the molecular basis for selectivity of these biocatalysts we obtained a high‐resolution crystal structure of selective Csp2−N bond forming dimerase, AspB. Overlay of the AspB structure onto C−C and C−N bond forming homolog NzeB revealed no significant structural variance to explain their divergent chemoselectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We synthesized a substrate derivative where the indole nitrogen was methylated, termed N1-methyl cWP (3) (Figure 3A), as computational studies by Sherman and colleagues have suggested that DKP-dimerization by AspB may be afforded by primary indole N-H abstraction. 19,23 AspB displayed very similar binding characteristics (K D and maximal spin-state conversion) with (3) (Figure S11). The crystal structure of N1-methyl cWP-bound AspB (PDB: 8TWU) was solved to 1.86 Å resolution (Figure S12A, Table S4).…”
Section: Inverse Steady-state Kinetic Solvent Isotope Effect Inmentioning
confidence: 84%
See 1 more Smart Citation
“…We synthesized a substrate derivative where the indole nitrogen was methylated, termed N1-methyl cWP (3) (Figure 3A), as computational studies by Sherman and colleagues have suggested that DKP-dimerization by AspB may be afforded by primary indole N-H abstraction. 19,23 AspB displayed very similar binding characteristics (K D and maximal spin-state conversion) with (3) (Figure S11). The crystal structure of N1-methyl cWP-bound AspB (PDB: 8TWU) was solved to 1.86 Å resolution (Figure S12A, Table S4).…”
Section: Inverse Steady-state Kinetic Solvent Isotope Effect Inmentioning
confidence: 84%
“…The C-N linkage of two molecules of cWP involves a twoelectron oxidation of the substrates, and mechanisms that are initiated by indole or DKP N-H abstraction by CYP-I have been advanced. 18,19,23 A structural alignment of AspB with other well-characterized CYP monooxygenases shows a distinct alteration of residues at the I-helix that are known to be critical for O-O heterolysis in O 2 -activating CYPs (Figures S1A,B). Notably, AspB lacks the highly conserved acid (Asp or Glu) on the I-helix distal pocket that forms half of the "acidalcohol pair" that is crucial for mediating proton delivery to the ferric peroxo-anion intermediate (Figure S1C).…”
Section: Inverse Steady-state Kinetic Solvent Isotope Effect Inmentioning
confidence: 99%
“…The results demonstrate that directed evolution improved selectivity and productivity in the catalysis of an unnatural amide-containing hexaketide substrate 1 and offers significant promise for expanding to other substrates with diverse functionalities, aiming to generate novel macrolactones, macrolactams, depsipeptides, and other TE-mediated biosynthetic systems. Moreover, future computational analysis through QM, molecular dynamics (MD) calculations and machine learning (ML) approaches [126][127][128][129][130][131] could provide new mechanistic insights relating to mutations identified in our of biocatalyst variants. These approaches could also predict additional amino acids that modulate selectivity in TEs beyond the amide hexaketide substrate 1.…”
Section: Discussionmentioning
confidence: 99%
“…We initially identified residues of potential importance for cyclization using the previously reported Pik TE WT crystal structure with a covalently bound pentaketide mimic, 34 which enabled target residues of interest to be identified for directed evolution. We expect that applying computational and ML-based approaches 40,[126][127][128][129] will deepen our mechanistic understanding of the cyclization process and the impact of select mutations on catalytic productivity. Moreover, our Pik TE variant library will provide an ongoing resource to identify efficient biocatalysts for varied hexaketide/heptaketide substrates with the goal of obtaining novel bioactive macrolides and related molecules.…”
Section: Discussionmentioning
confidence: 99%